Ticaret Anlaşmalarının Türkiye'nin İhracat Dinamiğine Etkisi: Yaygın ve Yoğun Ticaret - Kemal Türkcan; Erhan Pişkin (Turkish Economic Association, 2014)
– The present paper examines the effects of the Customs Union (CU) and Free Trade Agreements (FTAs) on Turkey's extensive and intensive margins. For this purpose, using highly disaggregated product-level data at the six-digit product level of Harmonized System, we first decompose Turkey's export to 172 countries over the period 1996-2011 into extensive and intensive margins, following the decomposition approach by Hummels and Klenow (2005). We then investigate the effects of the CU and FTAs on Turkey's extensive and intensive margins using a standard gravity model. The same analyses are carried out for different categories of goods (final goods and intermediate goods exports). The empirical analyses show that the effects of the CU and FTAs on the extensive and intensive margins are statistically significant. Furthermore, the results suggest that the CU has larger impact on the extensive and intensive margins than FTAs.
Keywords: F12; F14; F15; 330; Free Trade Agreements; Customs Union; Extensive Margin; Intensive Margin